Gender-inclusive Decision-Making Process in the Family and Community to Achieve Gender Equality in Ebonyi State, Nigeria - Ukah, Jonathan; Eteng, Mary; Eyisi, Emmanuel; Aboh, Fidelis; Okafor, Cynthia (Italian Sociological Review, 2026)
Gender inequality has been considered to be a global concern with a wide gap in the political and economic relations among men and women across the world. This has necessitated United Nations and other development agencies to make gender equality a top priority. This is exemplified by the inclusion of gender equality as number 5 goal of the sustainable development goals of United Nations. As part of achieving sustainable development goal Number 5, gender-inclusive decision-making process within the family and community in Ebonyi State, Nigeria was examined. The main thrust of the study was to ascertain how the educational level, income level and marital status of women influence their level of participation in the family and community decision making process. Descriptive survey design was adopted for the study. Structured questionnaire was used for data collection. A multi-stage sampling method was used to select households. Correlation and regression model were used for the analysis. The main result revealed that gender inequality exists in families and communities. From the findings only women with high income, high educational level and married women, indicated appreciable level of participation in family and community decisions, In conclusion, the study highlights the significant role of patriarchal culture in perpetuating gender inequalities in decision-making within families and communities in Nigeria. It is recommended that government and NGOs implement targeted awareness campaigns to challenge negative cultural norms. Further research should explore the effectiveness of such interventions and examine other factors that may influence women's participation in decision-making processes Key words: Decision making, family, gender equality, sustainable development goal, and women